Higher education in virtual worlds : teaching and learning in Second Life - Wankel, Charles; Kingsley, Jan (Emerald Group Pub., 2009)
The use of virtual world platforms is still in its infancy and many educators are wondering how best to use such platforms as a complement to their teaching and facilitation strategies. Targeted at educators and researchers wishing to use virtual environments in their teaching practice "Higher Education in Second Life" provides practical advice specifically for educators in higher education. This book focuses on the use of Second Life - a free, readily-accessible virtual world which is increasingly being used for both formal and informal learning. "Second Life" provides a platform where people can meet and collaborate, teach and learn, play roles and live through experiences. For the experienced this publication provides case studies and ideas for implementing effective learning experiences, for the novice it offers suggestions for overcoming potential barriers and joining the community of 'new frontier educators'. It has a broad appeal to educators from a wide range of disciplines, from the academic community, to training and development managers, and companies with corporate universities looking to reduce their costs through the use of technology and distance learning.